Ice Conditions at Cape Hatt, Baffin Island - Dickins, David F. (ARCTIC, 1987)
The ice environment at Cape Hatt was studied to determine annual variations in ice break-up and freeze-up, which could affect the design, execution and results of the Baffin Island Oil Spill Project. Data from lapse camera stations, field observations and historical charts were used to compare the Cape Hatt ice regime with other arctic sites and to assess the potential for ice interaction with oiled intertidal sediments. The Cape Hatt area experiences 63 days of open water in an average year and generally has a similar ice cycle to other inlets in the eastern Arctic. Ice deterioration begins in June, and the area is normally clear of ice by late July. Freeze-up begins in late September, and complete ice cover is established within a month of first ice formation. Given the 30% shorter open water period at Cape Hatt compared with more southerly arctic locations, the long-term oil weathering rates derived from the BIOS Project can be considered conservative when applied to areas such as the Beaufort Sea. The summer of 1981 was characterized by an unusually long open water season, and ice did not hinder field operations associated with the experimental oil releases. The variability in open water seasons during subsequent summers will be an important factor in determining the long-term fate of oil stranded in Bay 11. The interaction of ice with the nearshore seabed was observed to play a major role in mixing and redistributing the upper layer of beach material ranging from fine silt to boulders.Key words: Cape Hatt, ice break-up, ice freeze-up, time lapse, Baffin Island Mots clés: cap Hatt, débâcle, prise des glaces, photographies prises à intervalles, île Baffin